Methodology Of Developing Student’s Writing Skills with The Assistance of Independent Learning - Gulnoz Abduxalilovna Kayumova (Euro Asian Journal Publishing, 2024)
The article is devoted to the study of ways to develop selfeducation skills in English lessons at different stages of learning. The author gives a General description of each method and justifies their effectiveness
Keywords: pedagogy; self-education; English language; developing learning